STUDY OF SMALL BUSINESS POTENTIAL ORDER TO EMPOWER SMALL ENTREPRENEURS IN DISTRIS MEDAN DELI - Dewi Andriany (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The development of business /small industry gets serious attention from various groups,the governmenrt or the public,it is inseparable from the role in employment and small business resilience to shocks,such as the economic crisis in 1997 ago. Other than that small business also act as significant source of economic growth that directly helped create increased income neighborhoods.